1988
DOI: 10.1177/004947558801800302
|View full text |Cite
|
Sign up to set email alerts
|

Epidemics of Non-A, Non-B Hepatitis in Pakistan

Abstract: Three epidemics of acute viral hepatitis which occurred in different areas of Pakistan, namely Quetta, Mardan and Rawalpindi were studied. All the cases presented with jaundice, anorexia and nausea. The liver function tests showed raised serum bilirubin, alkaline phosphatase and ALT levels. In all the patients except one, the serology was consistent with non-A, non-B (NANB) hepatitis, which was most likely waterborne. This study shows that, as in some other parts of Asia and North Africa, epidemics of waterbor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

1994
1994
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 10 publications
0
8
0
Order By: Relevance
“…Abbottabad is located in the foothills of the Himalayan Mountains 116 km northwest of Rawalpindi and Islamabad and 217 km northeast of Peshawar in the Northwest Frontier Province (Figure 1). An investigative team from the PULSE in Rawalpindi joined members from the hospital in Abbottabad during an initial investigation from August 22 to 24,1988. Through August 23, 68 persons were hospitalized with a diagnosis of hepatitis (Figure 2), as manifested by anorexia, nausea, occasional vomiting, malaise, dark urine, and icterus.…”
Section: Methodsmentioning
confidence: 99%
“…Abbottabad is located in the foothills of the Himalayan Mountains 116 km northwest of Rawalpindi and Islamabad and 217 km northeast of Peshawar in the Northwest Frontier Province (Figure 1). An investigative team from the PULSE in Rawalpindi joined members from the hospital in Abbottabad during an initial investigation from August 22 to 24,1988. Through August 23, 68 persons were hospitalized with a diagnosis of hepatitis (Figure 2), as manifested by anorexia, nausea, occasional vomiting, malaise, dark urine, and icterus.…”
Section: Methodsmentioning
confidence: 99%
“…Available data indicates that in Pakistan, Hepatitis E virus (HEV) remains highly endemic throughout the year, mainly affecting the adult population [10] [11] and sporadic cases of hepatitis E occurs frequently. A number of mini-epidemics have been reported in Pakistan and most of these have been due to fecal contamination of water supply, including those reported in Karachi in 1985 and 1986 [4] [5]. Other major reported outbreaks of HEV in Pakistan were 250 cases reported in an Army battalion in 1972 [12], 3827 cases from general population reported in Islamabad in the year 1993 [13].…”
Section: Introductionmentioning
confidence: 99%
“…[31] HEV though less stable than HAV, can withstand high temperatures and can remain viable for years. [32] HEV infection in South Asian countries exhibited distinct seasonal pattern with rainy season exhibiting the highest number of cases. However a bimodal pattern of incidence of the disease had been observed in the present study with the highest rate of positivity of HAV infection was observed in the months July followed by March.…”
Section: Discussionmentioning
confidence: 98%